Digitalization in Indonesian Cooperatives: Is It Necessary? - Nurdany, Achmad; Prajasari, Anniza Citra (Universitas Airlangga, 2020)
Digitalization has already penetrated all sectors of life and dominates business models. This study evaluates the extent to which small businesses should adopt digitalization. We focus on the cooperative's business model currently fighting with another fast-growing and popular business model, the start-up. Then, we used direct field research, including descriptive analysis and in-depth interviews with cooperatives in the Yogyakarta Special Region, Indonesia. We found that that the use of digital media by cooperatives in our study was minimal. From in-depth interviews, we found that some non-digital cooperatives insist on not using digitalization due to the lack of digital media penetration of their targeted customers and a preference for word-of-mouth marketing. One practical implication of this study is that digitalization depends somewhat on the addressed customer market model. Keywords: Digitalization, Cooperatives, Word of Mouth JEL: D22, G23, O14